2011
DOI: 10.4102/jsava.v82i4.76
|View full text |Cite
|
Sign up to set email alerts
|

A study of some infectious causes of reproductive disorders in cattle owned by resource-poor farmers in Gauteng Province, South Africa

Abstract: Two hundred and thirty-nine cattle from Gauteng Province in South Africa were tested for various pathogens causing reproductive diseases including bovine viral diarrhoea/mucosal disease (BVD/MD) virus, infectious bovine rhinotracheitis/infectious pustular vulvovaginitis (IBR/IPV) virus, Neospora caninum and Brucella abortus using various tests. For BVD/MD virus, 49.37 % tested positive, 74.47 % for IBR/IPV virus, 8.96 % for Neospora caninum and 3.8 % for Brucella abortus. The result for Brucella abortus is hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 10 publications
1
18
2
Order By: Relevance
“…This technique could therefore stop the slaughtering of vaccinated animals in the Eastern Cape. Brucella vaccines used in South Africa for livestock are the B. melitensis Rev 1, the live B. abortus strain 19, and B. abortus strain RB51 [17]. One of the reasons S19 was detected in our study is due to the fact that it is the vaccine of choice in the Eastern Cape for the prevention of brucellosis in cattle because it has been reported to be superior [40].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This technique could therefore stop the slaughtering of vaccinated animals in the Eastern Cape. Brucella vaccines used in South Africa for livestock are the B. melitensis Rev 1, the live B. abortus strain 19, and B. abortus strain RB51 [17]. One of the reasons S19 was detected in our study is due to the fact that it is the vaccine of choice in the Eastern Cape for the prevention of brucellosis in cattle because it has been reported to be superior [40].…”
Section: Discussionmentioning
confidence: 70%
“…Reports on brucellosis in Southern Africa are mainly restricted to cattle with the exclusion of small ruminants (sheep and goats) and are widely based on serological surveys [16,17]. Consequently, this present study aimed at detecting and identifying Brucella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies already showed negligible percentages for the involvement of Campylobacter spp. in bovine abortion [34], [57]. More samples should be collected to survey the infections caused by these two bacteria in dairy herds.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, reports on neosporosis are limited; however, the available information is in line with global understanding of the protozoan that underscores the relevance of the N. caninum to the dairy sector (Ghalmi et al, 2012). The general seroprevalence of this disease globally ranges from 1.9 to 39.7% (Njiro et al, 2011;Ayinmode and Akanbi, 2013).…”
Section: Neosporosismentioning
confidence: 99%